Edukasi Terapi Benson untuk Mengurangi Tingkat Stres Kerja pada Karyawati di Pabrik Soun Scorpio Desa Karangsoka Kabupaten Banyumas - Tammami, Zakiatu; Sumarni, Tri; Kurniawan, Wasis Eko (Pusat riset dan Inovasi Nasional, 2025)
Stress can be defined as a condition of tension that affects various aspects of a person’s life. Work-related stress may be caused by several factors, such as excessive workload, tight deadlines, conflicts with colleagues, or uncertainty in the workplace. One method that can be applied to manage stress is the Benson Relaxation Technique. The Benson Technique is a relaxation method that helps relieve bodily tension, with the expectation of improving sleep quality and preparing individuals to achieve a deeper connection with the Creator or spiritual being. This community service activity aimed to provide education regarding the Benson Relaxation Technique to reduce work-related stress among female workers at Soun Scorpio Factory in Karangsoka Village. The methods used in this activity included measuring stress levels using a work stress instrument, assessing knowledge levels through pre-test and post-test questionnaires, and conducting evaluations using observation sheets. The activity involved 25 female workers at Soun Scorpio Factory who received education on the Benson Technique, delivered in two sessions. The evaluation results showed that 84% of the participants were in the moderate stress category, and 16% were in the low-stress category. Knowledge evaluation results indicated that 16 participants (64%) had good knowledge, while 9 participants (36%) had sufficient knowledge. After the intervention, all respondents (100%) showed a reduction in stress levels to the low-stress category. Thus, the Benson Relaxation Technique can serve as an effective approach to reducing work-related stress among female workers and improving their mental well-being.